Milgram-experiment with soldiers: The Western Occupying Group’s involvement in the Holocaust (Academic Journal of Internal Affairs, 2017)
The author provides an overview of how Hungarian forces became mass murderers in Ukraine in WWII.
Keywords: soldiers; Word War II.; mass murderers